Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1523/jneurosci.23-37-11759.2003
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Dependent Redistribution and Essential Role of Cortactin in Dendritic Spine Morphogenesis

Abstract: The number and shape of dendritic spines are influenced by activity and regulated by molecules that organize the actin cytoskeleton of spines. Cortactin is an F-actin binding protein and activator of the Arp2/3 actin nucleation machinery that also interacts with the postsynaptic density (PSD) protein Shank. Cortactin is concentrated in dendritic spines of cultured hippocampal neurons, and the N-terminal half of the protein containing the Arp2/3 and F-actin binding domains is necessary and sufficient for spine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
275
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(308 citation statements)
references
References 55 publications
32
275
1
Order By: Relevance
“…The volume of spines increased over 100% after Jasplakinolide treatment (Fig. 4b, d) (Hering and Sheng, 2003;Wang et al, 2007). Taken together, these results indicate that the fluorescence lifetime of the actin FRET sensor is a sensitive, selective and quantitative measure of actin polymerization.…”
Section: Actin Polymerization Quantified With the Megfp-sreach Pairmentioning
confidence: 54%
“…The volume of spines increased over 100% after Jasplakinolide treatment (Fig. 4b, d) (Hering and Sheng, 2003;Wang et al, 2007). Taken together, these results indicate that the fluorescence lifetime of the actin FRET sensor is a sensitive, selective and quantitative measure of actin polymerization.…”
Section: Actin Polymerization Quantified With the Megfp-sreach Pairmentioning
confidence: 54%
“…Cortactin expression supression 39 and CTTNBP2 knockdown in neurons 37 reduce the spine density 39 , indicating their importance for the formation and maintenance of the spines. Cortactin acts downstream of CTTNBP2 in spine morphogenesis, as the defects caused by CTTNBP2 knockdown can be rescued by cortactin overexpression but not by overexpressing a CTTNBP2 mutant protein that cannot bind cortactin 37 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Cortactin is an F-actin-binding protein and an activator of the Arp2/3 actin nucleation machinery [32,33]. Previous studies show that cortactin downregulation results in spine depletion, whereas its overexpression causes spine elongation [34]. It is also reported that overstimulation of NMDA receptors removes cortactin and thereby collapses dendritic spines, whereas stimulation with neurotrophic factors redistributes cortactin from dendritic shafts to spines to solidify synaptic transmission [35].…”
Section: Endophilin A1 Regulates Actin Cytoskeleton Reorganization Inmentioning
confidence: 99%